'Jistis ak Reparasyon pou Tout Viktim Kolera MINUSTAH':* The United Nations and the Right to Health in Haiti. (30th July 2015) - FREEDMAN, ROSA; LEMAY-HEBERT, NICOLAS
Abstract: The Haiti cholera claims are focused upon the UN's violation of the rights of individuals affected by the cholera outbreak to access a remedy. The UN's absolute immunity from jurisdiction of national courts is counterbalanced by its duty to provide alternative dispute resolution mechanisms for private law claims. The UN has not only failed to provide those alternative dispute resolution mechanisms, but has repeatedly stated that no claims are receivable in these circumstances. Here we set out that even if the UN is able to shield itself from private law claims by using the cloak of absolute immunity, the UN might be held responsible for human rights violations arising from the cholera outbreak in Haiti. This article is concerned with the broader issue of whether the UN has violated and continues to violate individuals' right to health in Haiti.